2018
DOI: 10.1177/0963689718817219
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Role of miRNA-144-3p in Intracerebral Hemorrhage Induced Secondary Brain Injury is Mediated by Formyl Peptide Receptor 2 Downregulation Both In Vivo and In Vitro

Abstract: Although microRNA-144-3p (miRNA-144-3p) has been shown to suppress tumor proliferation and invasion, its function in intracerebral hemorrhage (ICH)-induced secondary brain injury (SBI) remains unclear. Thus, this study was designed to investigate the role of miRNA-144-3p in ICH. To accomplish this, we used adult male Sprague-Dawley rats to establish an in vivo ICH model by injecting autologous blood, while cultured primary rat cortical neurons were exposed to oxyhemoglobin (OxyHb) to mimic ICH in vitro. To exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…We confirmed that RvD1 had a direct protective effect on primary neurons, which was primary reflected in the improvements in cell viability, inhibition of the production of oxidative stress products, the avoidance of synaptic injury and a reduction in cell death induced by Hb. These results were consistent with those of previous studies [50,53,54]. For example, Peritore et al observed that ALX/FPR2 gene knockout significantly increased the apoptosis of brain neurons in a depression model [50].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We confirmed that RvD1 had a direct protective effect on primary neurons, which was primary reflected in the improvements in cell viability, inhibition of the production of oxidative stress products, the avoidance of synaptic injury and a reduction in cell death induced by Hb. These results were consistent with those of previous studies [50,53,54]. For example, Peritore et al observed that ALX/FPR2 gene knockout significantly increased the apoptosis of brain neurons in a depression model [50].…”
Section: Discussionsupporting
confidence: 93%
“…However, the results of some other relevant studies might provide some indications. For instance, Fan et al showed that RvD1 functioned through the PI3K-Akt-caspase-3 pathway in rats with cerebral hemorrhage in vivo and neuronal Hb stimulation in vitro [54]. However, there are few relevant results for other signaling pathways, which need further study in future.…”
Section: Discussionmentioning
confidence: 99%
“…Formyl peptide receptor 2 (FPR2), a classical chemoattractant receptor of G-protein-coupled receptors, is reported to be involved in cell proliferation and migration in some diseases. 12 A recent study showed that FPR2 had a robust effect on attenuating brain damage and promoting nerve regeneration, 13 and it has been reported that formyl peptide receptors (FPR) enhance the migration and differentiation of rat neural stem cells. 14 The biological effects of ANXA1 are mediated through FPRs.…”
mentioning
confidence: 99%
“…In addition to their diagnostic uses, miRNA could also be used in the treatment of ICH (Jeyaseelan et al, 2007). The over-expression of miR-144-3p aggravates neurological injury after ICH through neuronal apoptosis by the PI3K/AKT pathway (Fan et al, 2018). Moreover, miR-23a-3p has been reported to promote edema formation after ICH via ZO-1 (Hu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%